Shear Mechanism of High-Strength-Friction-Grip Bolts in Steel and Steel-Fiber-Reinforced-Concrete Composite Beams - Zhang, Yujie; Zhang, Junping; Chen, Bingcong; Zhang, Yumin (Frontiers in Materials, 2022)
Steel and steel-fiber-reinforced concrete (SFRC) composite beams with high-strength friction-grip bolt (HSFGB) connectors have been found to improve the shear behavior of HSFGBs and enhance the potential application of composite beams. In order to evaluate the shear force transmission mechanism of HSFGBs in steel-SFRC beams, finite element models (FEMs) developed by ABAQUS software had been carefully developed to evaluate force transmission and failure mechanisms of HSFGBs. Shear behavior differences between conventional studs and HSFGBs were also studied. Then according to the orthogonal statistics method, FEMs were further modified to explore significant influencing factors affecting HSFGB shear performance. The results showed that pretension degree was the main factor affecting the shear performance of HSFGBs at serviceability limit states, while HSFGB diameter was the most important factor affecting stiffness and ultimate shear strength at ultimate limit state.